2021
DOI: 10.1111/os.12762
|View full text |Cite
|
Sign up to set email alerts
|

Knee Prosthesis in the Computer Era

Abstract: Over the past two decades, computer assistance has revolutionalized surgery and has enabled enormous advancements in knee prosthesis surgery. Total knee arthroplasty (TKA) is a hot topic of orthopaedic research. Reflecting population dynamics, its use continues to increase, especially in high demand populations. Therefore, efforts to achieve the best fit and precise alignment in TKA continue. Computer assistance is valuable for knee prosthesis surgeons in this regard. This manuscript investigated the use of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…T otal knee arthroplasty (TKA) is the only effective treatment for end-stage knee osteoarthritis. While many surgeons follow Install and Ranawat's mechanical alignment principle (IRMP) 1 to achieve a durable and successful TKA 2,3 , 20% of patients are not satisfied with their results. 4,5 The IRMP refers to two lines on the coronal plane of the lower limb: the vertical force line (referring to making osteotomies of the distal femur and proximal tibia) and the joint line (a line at the keen joint level perpendicular to the vertical force line obtained after the prosthesis has been implanted).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…T otal knee arthroplasty (TKA) is the only effective treatment for end-stage knee osteoarthritis. While many surgeons follow Install and Ranawat's mechanical alignment principle (IRMP) 1 to achieve a durable and successful TKA 2,3 , 20% of patients are not satisfied with their results. 4,5 The IRMP refers to two lines on the coronal plane of the lower limb: the vertical force line (referring to making osteotomies of the distal femur and proximal tibia) and the joint line (a line at the keen joint level perpendicular to the vertical force line obtained after the prosthesis has been implanted).…”
Section: Introductionmentioning
confidence: 99%
“…Total knee arthroplasty (TKA) is the only effective treatment for end‐stage knee osteoarthritis. While many surgeons follow Install and Ranawat's mechanical alignment principle (IRMP) 1 to achieve a durable and successful TKA 2 , 3 , 20% of patients are not satisfied with their results. 4 , 5 …”
Section: Introductionmentioning
confidence: 99%
“…TKA is a widely performed, mature, and effective orthopaedic surgery, which is often used to correct knee joint deformity, remove knee joint pain, and restore knee joint function 12 , 13 , 14 . The standard approach for TKA is the MPA.…”
Section: Discussionmentioning
confidence: 99%
“…There is an abundance of evidence that computer navigation produces better precision than conventional instrumentation, but only limited evidence that this translates into better clinical outcomes ( 36 ). Although recent reviews revealed the superiority of the navigation-TKA technique over the conventional technique remains uncertain in the short and long term, the use of computer navigation TKA is an example of an initiative to augment human decision-making and surgical handicraft with artificial intelligence ( 37 ).…”
Section: Discussmentioning
confidence: 99%